(untitled) (Международный научный журнал «Инженер», 2026)
90-91% of the water resources in our country are focused on agriculture. More than 80% of the inter-farm irrigation channels are soil-dominated, and 30-35% of the water in these channels is lost by filtration. Studies suggest that the useful operating coefficient of irrigation networks is on average 0.63, indicating the need to improve the efficiency of water resource utilization. In this article, the hydraulic efficiency of the inter-farm irrigation channels located in the Tashkent region was assessed by taking natilas in field conditions. Ways were proposed to determine water consumption in canals, calculate filtration losses, and improve efficiency.